Salmonella enterica serovar Typhi and gallbladder cancer: a case–control study and meta‐analysis. (11th October 2016) - Koshiol, Jill; Wozniak, Aniela; Cook, Paz; Adaniel, Christina; Acevedo, Johanna; Azócar, Lorena; Hsing, Ann W.; Roa, Juan C.; Pasetti, Marcela F.; Miquel, Juan F.; Levine, Myron M.; Ferreccio, Catterina; et al.
Abstract: In Chile, where gallbladder cancer (GBC) rates are high and typhoid fever was endemic until the 1990s, we evaluated the association between Salmonella enterica serovar Typhi ( S.  Typhi) antibodies and GBC. We tested 39 GBC cases, 40 gallstone controls, and 39 population‐based controls for S . Typhi Vi antibodies and performed culture and quantitative polymerase chain reaction for the subset with bile, gallstone, tissue, and stool samples available. We calculated gender and education‐adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for the association with GBC. We also conducted a meta‐analysis of >1000 GBC cases by combining our results with previous studies. GBC cases were more likely to have high Vi antibody titer levels than combined controls (OR: 4.0, 95% CI: 0.9–18.3), although S.  Typhi was not recovered from bile, gallstone, tissue, or stool samples. In our meta‐analysis, the summary relative risk was 4.6 (95% CI: 3.1–6.8, P heterogeneity =0.6) for anti‐Vi and 5.0 (95% CI: 2.7–9.3, P heterogeneity  = 0.2) for bile or stool culture. Our results are consistent with the meta‐analysis. Despite differences in study methods (e.g., S.  Typhi detection assay), most studies found a positive association between S . Typhi and GBC. However, the mechanism underlying this association requires further investigation Abstract : Gallbladder cancer (GBC) cases in Chile were more likely to have high Salmonella enterica serovar Typhi (S. Typhi) Vi antibody titer levels than population‐based controls and gallstone controls. These findings are consistent with meta‐analytic results identifying a four‐ to fivefold increased risk of GBC with S. Typhi exposure. Understanding the nature of the association between Salmonella enterica serovar Typhi and GBC may help inform public health policies for S. Typhi carriers.